Peran Keluarga Dalam Mengambil Keputusan Untuk Mengatasi Risiko Jatuh Pada Pasien Hipertensi - Etikasari, Nur; , Vinami Yulian, Ns., M.sc.Nursing (2016)
The disease is an abnormal state in the body or mind that causes discomfort, dysfunction or difficulty to those it affects. There are several types of infectious diseases, non-communicable diseases and chronic diseases. One non-communicable diseases are becoming a very serious health problem today is hypertension. Genesis falls themselves can occur and a fatality is not realized by a person with hypertension who are conducting activities and may result in loss of consciousness, stroke or physical weakness. The role of the family for a family member suffering from hypertension is by giving love and a sense of security, meet the needs of nutrition, physical health care, and generate impetus and vigor. The authors are able to implement and gain knowledge as well as experience regarding cases of hypertension in the community and family. The method used was descriptive case study that the scientific method is to collect data, analyze the data and draw conclusions. After being given the actions of family nursing three times meeting for 60 minutes, the family was willing and able to change the home environment by cleaning the bathroom floor of moss that was not slippery, smoke in the house and then the family continued to monitor and motivate in order to always maintain their health and high blood pressure. The success of family nursing process will be achieved when every member of the cooperative in continuing nursing process, then the family is willing and able to change the bad habits that can harm health. All family nursing actions that have been granted in accordance with the care plan such as progressive relaxation and exercise hypertension in theory and in research can reduce pain.